Isolamento e seleção de leveduras promotoras de crescimento vegetal de solo sob cultivo de milho orgânico - Bispo, Rafaela Letícia Brito (2022)
The microorganisms that promote plant growth are a group naturally found in beneficial association with plants, among which, yeasts have shown promising results. The objective of this work was to isolate, select and characterize yeasts from soil cultivated with corn (single and intercropped, with and without organic fertilization). The isolates were selected for their ability to produce indoleacetic acid (IAA), solubilize phosphate and control phytopathogenic fungi in vitro and were phenotypically characterized. The selected strains were identified by sequencing of the D1/D2 domain in the 26S gene of the ribosomal DNA and evaluated to produce AIA, solubilization of tricalcium phosphate and the effects of the suspension of cells or metabolites in the treatment of corn seeds. The strains identified were: Torulaspora delbrueckii (MGA9, maize + pigeon pea), Torulaspora globosa (MP18, maize + compost), Torulaspora delbrueckii, (MCP22, maize + sunn hemp + compost), Aureobasidium melanogenum (MA5, single maize), Candida pseudointermedia (MGA12, corn + pigeon pea), Trichosporon asahii (MCP24, corn + sunn hemp + compost) and Cryptococcus laurentii (MGCP25, corn + pigeon pea + sunn hemp + compost). The strains MCP22 and MGA9 stood out in terms of AIA productivity in potato broth and molasses. For all strains, the NBRIP culture medium offered the best conditions for the solubilization of tricalcium phosphate, except for the MA5 strain. In in vivo tests, no treatment affected seed germination. For the development of the radicle and coleoptile, there was greater development in the treatments with the metabolites of the MGA9 and MCP22 strains but resulted in plants with shorter shoot length. Regarding the root parameter, the metabolites of the MCP22 strain stood out, but resulted in plants with lower root dry mass. The best results were presented by the cells of the MCP22 strain and the cells and metabolites of MA5. It is possible to conclude that yeasts isolated from soil cultivated with corn present mechanisms of plant growth promotion and affect the development of the culture since its beginning, therefore, more studies are necessary to evaluate the potential for plant production.